2018
DOI: 10.1016/j.stemcr.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Donor- or Stem Cell-Derived Cone Photoreceptors Can Both Integrate and Undergo Material Transfer in an Environment-Dependent Manner

Abstract: SummaryHuman vision relies heavily upon cone photoreceptors, and their loss results in permanent visual impairment. Transplantation of healthy photoreceptors can restore visual function in models of inherited blindness, a process previously understood to arise by donor cell integration within the host retina. However, we and others recently demonstrated that donor rod photoreceptors engage in material transfer with host photoreceptors, leading to the host cells acquiring proteins otherwise expressed only by do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 36 publications
(126 reference statements)
5
84
1
1
Order By: Relevance
“…At 3 weeks post‐transplantation into the subretinal space of 8 to 10‐week‐old Pde6brd1 mice, human GFP + cells expressing the pan‐photoreceptor marker Recoverin were found in a distinct outer nuclear like layer in direct contact with the host secondary order neurons. Some of the transplanted human CRX + cells displayed the expression of pan cone photoreceptor marker, Arrestin 3, and cone opsins, which indicates further differentiation to more mature cones upon transplantation and corroborates recent data obtained with mouse ESC and retinal‐derived CRX‐GFP + photoreceptor precursors . Since no cones were found in the host retina, it is impossible for the CRX‐GFP + to have acquired the cone fate through cellular transfer.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At 3 weeks post‐transplantation into the subretinal space of 8 to 10‐week‐old Pde6brd1 mice, human GFP + cells expressing the pan‐photoreceptor marker Recoverin were found in a distinct outer nuclear like layer in direct contact with the host secondary order neurons. Some of the transplanted human CRX + cells displayed the expression of pan cone photoreceptor marker, Arrestin 3, and cone opsins, which indicates further differentiation to more mature cones upon transplantation and corroborates recent data obtained with mouse ESC and retinal‐derived CRX‐GFP + photoreceptor precursors . Since no cones were found in the host retina, it is impossible for the CRX‐GFP + to have acquired the cone fate through cellular transfer.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to developmental maturation, it is of interest to investigate the role of host retina. In this study, we used a model of fast retinal degeneration to ensure lack of host photoreceptors and minimize the likelihood of material transfer between host and donor photoreceptors, thus enhancing the possibility of hESC‐derived photoreceptor precursor engraftment . We performed immunocytochemistry using two different antibodies to HNAs and in both cases we observed colocalization with the CRX immunostaining and endogenous GPP expression, thus demonstrating that these cells were not endogenous mouse photoreceptors and did not arise through material transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have suggested that stem cell-derived exosomes and exosomal microRNAs (miR-144-5p) inhibit ovarian cell apoptosis [4][5][6]. Recently, several studies noted that material transfer between host and donor cells accounts for the rescue effect of stem cell therapy [7,8]. Additionally, we cannot rule out the possibility that transplanted stem cells may integrate into host ovaries, differentiate into ovarian cells, and replace the impaired cells of the recipients.…”
Section: Introductionmentioning
confidence: 87%